PROJETO REGULARIZAÇÃO FUNDIÁRIA URBANA - Pettenon, Gabrielli Marques; Dal Molin, Isabella; Moura, Patricia; Oliveski, Patricia Marques; Schneider, Eliete Vanessa (Salão do Conhecimento, 2019)
Projeto de extensão no curso de Direito da Unijuí